Soil Erosion as A Result of Upland Traditional Cultivation in Java Island - Hardjono Hardjowotjitro (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 1981)
Soil erosion is one of the most important problems in the world. History, tradition, area condition, and differencies of the intensity of soil erosion measures cause differencies in quantity of erosion in one place and the other. Also the variation of the kind of the occasion problems, will result diferencies in the kind of prevention activities too. Soil erosion in Java Island caused by specific reasons i.e. traditional agriculture cultivation pattern without taking into account any soil conservation measures and proper landuse, and influenced by the bad condition of the population pattern because of the intense increasing population density, and about 70 percent of the inhabitants have their living solely from agriculture cultivation. From the knowledge of the quantity of erosion in Java based on the results of the available observations, and the problems causing it, can be expected to find a correct step and operational strategy of prevention. The prevention of erosion in Java is not only an introduction effort and to create awareness and technical knowledge among the farmers, but this should be combined with other activities i.e. transmigration, birth control, increase of income, creation of new employment opportunity, etc.